Prevention of Tabzir in Muslim Households Food Consumption - Lubis, Deni; Rodoni, Ahmad; Amalia, Euis (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
Islam forbids tabzir (wasteful behavior) concerning food and all activities. However, Indonesia, which has a Muslim-majority population, is among the countries with the highest levels of food loss and waste globally. Food waste has a detrimental impact on the environment, economy, human health, and food security, hindering the achievement of the SDGs. This study aims to examine Muslim households' consumption patterns and identify food waste prevention strategies. A qualitative SWOT-ANP technique was applied using nine respondents, including experts, academics, and practitioners. The findings suggest that households, from an internal perspective, should prioritize sharing surplus food with those in need, as well as adopting thoughtful shopping and cooking habits, avoiding the tendency to over-purchase or over-prepare food. Three external strategies were identified: (1) campaigns by governments, agencies, and communities to raise awareness of food waste's negative effects; (2) education on proper food processing, storage, and management; (3) policies regulating food waste prevention and management. Ultimately, preventing food waste behavior requires the collaboration of all parties, including the government, religious authorities, communities, and households.